Women attorneys and the changing workplace : high hopes, mixed outcomes - Kitzerow, Phyllis (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2014)
A half-century ago, women comprised only a tiny fraction of practicing attorneys. Today, nearly half of law school graduates are female. Phyllis Kitzerow explores the experiences of women in the legal profession over the past fifty years, charting the sometimes surprising impact of shifting social norms on pathways to professional and personal success. Kitzerow contrasts the experiences of women across generations, showing how the backgrounds and expectations of each cohort--from the pioneers of the 1960s to women starting out today--have played out in the evolving legal profession. Her analysis offers important lessons on a range of contentious work-related issues, on the meanings of success, and on the ways that individuals make the best of the options available to them.